DECONSTRUCTING IMAGES AND TRANSFORMING STORIES: WOMEN WHO CHALLENGE GENDER STEREOTYPES IN ARTISTIC PRACTICES (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
This research dives into video art as a medium of expression and disruption of gender stereotypes, focusing on the work of women artists. It analyzes the convergence between video art and the redefinition of gender roles, exploring how women artists use this medium to challenge and deconstruct entrenched stereotypes. This research seeks to delve deeper into this phenomenon, highlighting the critical role of video art in the transformation of gender narratives and perceptions.
Keywords: Video art; audiovisual technology; women artists; gender stereotypes; cultural transformation